Heme oxygenase‐1 regulates sirtuin‐1–autophagy pathway in liver transplantation: From mouse to human. Issue 5 (18th December 2017) - Nakamura, Kojiro; Kageyama, Shoichi; Yue, Shi; Huang, Jing; Fujii, Takehiro; Ke, Bibo; Sosa, Rebecca A.; Reed, Elaine F.; Datta, Nakul; Zarrinpar, Ali; Busuttil, Ronald W.; Kupiec‐Weglinski, Jerzy W.
Abstract : Liver ischemia–reperfusion injury (IRI) represents a major risk factor of early graft dysfunction and a key obstacle to expanding the donor pool in orthotopic liver transplantation (OLT). Although graft autophagy is essential for resistance against hepatic IRI, its significance in clinical OLT remains unknown. Despite recent data identifying heme oxygenase‐1 (HO‐1) as a putative autophagy inducer, its role in OLT and interactions with sirtuin‐1 (SIRT1), a key autophagy regulator, have not been studied. We aimed to examine HO‐1–mediated autophagy induction in human OLT and in a murine OLT model with extended (20 hours) cold storage, as well as to analyze the requirement for SIRT1 in autophagy regulation by HO‐1. Fifty‐one hepatic biopsy specimens from OLT patients were collected under an institutional review board protocol 2 hours after portal reperfusion, followed by Western blot analyses. High HO‐1 levels correlated with well‐preserved hepatocellular function and enhanced SIRT1/LC3B expression. In mice, HO‐1 overexpression by genetically modified HO‐1 macrophage therapy was accompanied by decreased OLT damage and increased SIRT1/LC3B expression, whereas adjunctive inhibition of SIRT1 signaling diminished HO‐1–mediated hepatoprotection and autophagy induction. Our translational study confirms the clinical relevance of HO‐1 cytoprotection and identifies SIRT1‐mediated autophagy pathway as a new essential regulator of HO‐1 function in IR‐stressed OLT. Abstract : This translational study confirms the clinical relevance of heme oxygenase‐1 hepatoprotection and identifies SIRT1‐dependent autophagy signaling as a novel and essential regulator of HO‐1 function in liver transplant under ischemia–reperfusion stress.